2007
DOI: 10.1111/j.1468-2850.2007.00094.x
|View full text |Cite
|
Sign up to set email alerts
|

Emotion and evolving treatments for adult psychopathology.

Abstract: Clinical psychology has historically underplayed the importance of emotions in conceptualizing and treating adult psychopathology. However, there has been a recent convergence among numerous theoretical orientations in drawing from investigations of emotions within basic affective sciences, which highlight the survival and societal functions of emotions, the involvement of multiple biological systems in emotion generation, and a dynamic model for regulatory aspects of emotions. These characterizations of emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
105
0
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(122 citation statements)
references
References 158 publications
3
105
0
9
Order By: Relevance
“…The affective sciences are converging in the assumption that emotions are functional in that they are generated in response to motivationally salient stimuli (Gross, 2014;Mennin & Farach, 2007;Scherer, 2000). As such, avoiding emotional experiences may prevent an individual from gaining access to the information held by emotions about the situation and possible courses of action (Kashdan, Barrett, EMOTION REGULATION FLEXIBILITY IN SAD 13 & McKnight, 2015;Mennin & Fresco, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The affective sciences are converging in the assumption that emotions are functional in that they are generated in response to motivationally salient stimuli (Gross, 2014;Mennin & Farach, 2007;Scherer, 2000). As such, avoiding emotional experiences may prevent an individual from gaining access to the information held by emotions about the situation and possible courses of action (Kashdan, Barrett, EMOTION REGULATION FLEXIBILITY IN SAD 13 & McKnight, 2015;Mennin & Fresco, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, simply talking about emotions, when this is done in a highly intellectualized or emotionally distant way, is usually insufficient to produce emotional change. ST makes prominent use of experiential techniques in order to bring emotions into active awareness and overcome emotional distance (Leahy, 2007;Mennin & Farach, 2007;Warwar, Links, Greenberg, & Bergmans, 2008). In fact, experiential, or emotion-focused, techniques are one of the hallmarks of ST, which distinguish it from more traditional cognitive-behavioral therapy approaches.…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…In recent decades there has been increased interest in affective phenomena in psychopathology and emotion-regulatory strategies incorporated into psychopathology models [6][7][8][9][10] . Emotion regulation is defined as a mixture of conscious and unconscious processes by which individuals modulate their emotions to appropriately respond to environmental stress [1,[11][12][13][14][15] .…”
Section: Conceptual Foundation Emotion Regulationmentioning
confidence: 99%
“…The well known stress-vulnerability model of aetiological impact in psychiatry suggests that due to genetic or psychological predispositions individuals who are selectively vulnerable to environmental risks respond to stressors with increasing levels of emotional distress and by mobilizing psychosocial resources [4,5,17,18] . From the stress-process perspective, the distress-related disorders are viewed as the outcome of emotion dysregulation [9,11,14] . Several researchers have also empirically demonstrated that individuals who are unable to effectively manage their emotional responses to external or internal stresses, experience more severe and protracted periods of emotional distress that may evolve into diagnosable depression or anxiety disorders [5,9,19,20] .…”
Section: Conceptual Foundation Emotion Regulationmentioning
confidence: 99%
See 1 more Smart Citation